Muhammadiyah Green School di SMK Muhammadiyah 2 Turi Menuju Sekolah Adiwiyata - Septi Nur Wijayanti; Agus Nugroho Setiawan; Anisa Dwi Makrufi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
SMK Muhammadiyah 2 Turi launched the Adiwiyata school program, which is promoting knowledge and awareness about environmental conservation efforts among the student, and one way to make this happen is through the Muhammadiyah Green School (MGS). MGS is a concept that invites all stakeholders to form a lifestyle so that they care more about their environment. The problem is that the insights and skills of most of the stakeholders of SMKM 2 Turi on MGS are still limited. This community service program aims to increase knowledge and skills, and increase student and teacher awareness of the environment. This community service will be carried out in 2021 using a community development and participatory approach. The MGS program at SMK Muhammadiyah 2 Turi was conducted with several activities, i.e. coordination, focus group discussions, workshops, implementation, as well as mentoring and monitoring. With assistance from UMY, the MGS can improve the knowledge and skills of students and teachers in running MGS, the school environment is more conducive and productive, can become a medium for character education and cares for a clean and healthy environment, is able to provide space and learning materials for students, and be the first step towards Adiwiyata School